Primitive reflexes in infants with cerebral palsy due to Congenital Zika Syndrome and its relationship with other motor features - Serra, Leticia; Rios, Débora Patrícia; Rios, Mino; de Almeida, Breno Lima; Fernandes, Kelly de Souza; Lucena, Rita; de Siqueira, Isadora Cristina (Frontiers in Pediatrics, 2025)
BackgroundThe Zika virus outbreak, which occurred from 2015 to 2016 in Brazil, resulted in the birth of neonates with brain malformations arising from Congenital Zika Syndrome (CZS). The characterization of primitive reflexes and their relationships with other motor characteristics, easily clinically detectable by health professionals, can aid in establishing motor prognosis in affected children.ObjectiveTo describe reflex patterns in children with Cerebral Palsy (CP) due to CZS, and investigate associations with other motor features. Method: Observational cross-sectional study involving infants with CZS aged between 12 and 36 months. Primitive reflexes, protective reaction and markers of motor phenotype were evaluated.Results48 children, median age: 19 months, were enrolled, most (79.2%) presented very severe CP (GMFCS 5), the persistence of more than 5 primitive reflexes (55%) and motor development age between 3 and 6 months (33.3%) (Bayley-III). A reduced ability to acquire motor skills was associated with the total number of persistent reflexes (rho = −0.45, p < 0.01). Asymmetrical Tonic Neck Reflex (ATNR) correlated with GMFCS level (rho = 0.49, p < 0.001). Lower motor development age was linked to abnormal posturing (p < 0.001) and absence of Parachute Reaction (p < 0.001).ConclusionInfants with CP due to CZS present severe motor abnormalities. Lower motor development age is associated with the persistence of more than 5 primitive reflexes, abnormal posturing and the absence of Parachute Reaction. Parachute Reaction appears to be a prognostic marker of motor impairment severity in CZS-affected infants.